Intrusion detection and prevention in wireless sensor networks - Abduvaliyev, Abror; Pathan, Al-Sakib Khan; Zhou, Jianying; Roman, Rodrigo; Wong, Wai-Choong (CRC Press, 2013)
Due to the inherent features and weaknesses of Wireless Sensor Networks (WSNs) and the specific threats that target them, there have been many specially designed security protocols and mechanisms, such as Intrusion Detection Systems (IDSs), where correctness and energy efficiency are of vital importance. This chapter surveys recently proposed works on Intrusion Detection Systems in WSNs, and presents a comprehensive classification of various IDS approaches according to their employed detection techniques. The three main categories explored in this chapter are anomaly detection, misuse detection, and specification-based detection protocols. We give a description of existing security attacks in WSNs and the corresponding proposed IDS protocols to tackle those attacks. We analyze the works with respect to network architecture and highlight certain critical shortcomings that IDSs have. In addition, we define future research tracks for IDSs in wireless sensor networks. Though a few restricted survey works on this topic have already been done, we feel that there is a great need of performing a detailed and comprehensive study on the various facets so that the IDS in WSN could be analyzed from all the ‘need-to-know’ angles, thereby benefiting both generalists and specialists.